2021
DOI: 10.1242/jeb.232157
|View full text |Cite
|
Sign up to set email alerts
|

Pendulum-based measurements reveal impact dynamics at the scale of a trap-jaw ant

Abstract: Small organisms can produce powerful, sub-millisecond impacts by moving tiny structures at high accelerations. We developed and validated a pendulum device to measure the impact energetics of microgram-sized trap-jaw ant mandibles accelerated against targets at 105 m s−2. Trap-jaw ants (Odontomachus brunneus; 19 individuals; 212 strikes) were suspended on one pendulum and struck swappable targets that were either attached to an opposing pendulum or fixed in place. Mean post-impact kinetic energy (energy from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Longo et al, 2021;Nüchter et al, 2006;Pringle et al, 2005). Likewise, when measuring flow from energy source to environment, such as through puncture, impact and cavitation, the requisite sample rates for sensors are high (10 5 -10 6 samples per second) (Jorge et al, 2021;Patek and Caldwell, 2005). Substantial technical improvements in extreme highspeed imaging, dynamic sensing and unrestrictive analog to digital data acquisition sample rates (McHenry and Hedrick, 2023) have allowed researchers to increasingly focus on in vivo experiments with real-time spring and latch dynamics, resulting in an exciting uptick in the pace of discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Longo et al, 2021;Nüchter et al, 2006;Pringle et al, 2005). Likewise, when measuring flow from energy source to environment, such as through puncture, impact and cavitation, the requisite sample rates for sensors are high (10 5 -10 6 samples per second) (Jorge et al, 2021;Patek and Caldwell, 2005). Substantial technical improvements in extreme highspeed imaging, dynamic sensing and unrestrictive analog to digital data acquisition sample rates (McHenry and Hedrick, 2023) have allowed researchers to increasingly focus on in vivo experiments with real-time spring and latch dynamics, resulting in an exciting uptick in the pace of discovery.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, trap-jaw ants close their jaws at ultrafast speeds, using these impacts for multiple purposes, from capturing soft-bodied prey to escaping predation by propelling themselves off hard substrates ( Spagna et al, 2009 ). By studying the kinematics of trap-jaw ant impacts, Jorge et al (2021) found that jaw closure transferred more energy to stiff targets than to compliant ones, showing how the same impact, delivered to different materials, can achieve different biological tasks.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, trap-jaw ants close their jaws at ultrafast speeds, using these impacts for multiple purposes, from capturing soft-bodied prey to escaping predation by propelling themselves off the hard substrate (Spagna et al, 2009). By studying the kinematics of trap-jaw ant impacts, (Jorge et al, 2021) found that jaw closure transferred more energy to stiff targets than compliant ones, showing how the same impact, delivered to different materials, can achieve different biological tasks.…”
Section: Introductionmentioning
confidence: 99%